Massification of Higher Education in Malaysia: Challenges Facing Public Schools - Arnida Abdullah (TARBIYA: Journal of Education in Muslim Society, 2018)
AbstractHigher education plays an important role in many developing countries. Graduates are being equipped with professional knowledge and skills to fulfil the demands of the labour market in a knowledge economy. Malaysia is amongst those developing nations that have looked to advanced economies to provide a model of mass higher education which would raise educational levels and national income. Since the 1990s, therefore, the government has been expanding the higher education sector and broadening access to higher education institutions. Its goal is to boost higher education enrollments rate from 48 percent to 70 percent by the year 2025 (Ministry of Education Malaysia, 2015). The need to respond to this expansion of higher education enrolments has implications for all three levels of school education - primary, lower secondary and upper secondary. Using secondary data, this study aims to explore challenges currently facing public schools in order to produce graduates with good academic results that enable them to gain a place in higher institutions. The findings of this study have provided evidence that school education system is still facing great challenges. A key to making higher education more effective, therefore, is to strengthen and improve Malaysia’s public schools.AbstrakPendidikan tinggi memainkan peran penting di banyak negara berkembang. Para lulusan sedang dilengkapi dengan pengetahuan dan keterampilan profesional untuk memenuhi tuntutan pasar tenaga kerja dalam pengetahuan ekonomi. Malaysia adalah salah satu negara berkembang yang telah mencari ekonomi maju untuk menyediakan model pendidikan tinggi massal yang akan meningkatkan tingkat pendidikan dan pendapatan nasional. Sejak 1990-an, oleh karena itu, pemerintah telah memperluas sektor pendidikan tinggi dan memperluas akses ke institusi pendidikan tinggi. Tujuannya adalah untuk meningkatkan tingkat pendaftaran pendidikan tinggi dari 48 persen menjadi 70 persen pada tahun 2025 (Departemen Pendidikan Malaysia, 2015). Kebutuhan untuk menanggapi perluasan pendaftaran pendidikan tinggi ini berimplikasi pada ketiga tingkat pendidikan sekolah-sekolah dasar, menengah bawah, dan menengah atas. Penelitian ini bertujuan untuk mengeksplorasi tantangan yang saat ini dihadapi sekolah umum untuk menghasilkan lulusan dengan hasil akademik yang baik yang memungkinkan mereka mendapatkan tempat di institusi yang lebih tinggi. Temuan penelitian ini telah memberikan bukti bahwa sistem pendidikan sekolah masih menghadapi tantangan besar. Oleh karena itu, kunci untuk membuat pendidikan tinggi lebih efektif adalah memperkuat dan meningkatkan sekolah-sekolah negeri di Malaysia. How to Cite : Abdullah, A. (2018).  Massification of Higher Education in Malaysia: Challenges Facing Public Schools. TARBIYA: Journal of Education in Muslim Society, 5(2), 225-235. doi:10.15408/tjems.v5i2.8118.